SISTEM PENDUKUKUNG KEPUTUSAN PEMILIHAN SALON MOBIL TERBAIK DENGAN MENGGUNAKAN METODE WASPAS - Afrian Alfariz; Ibnu Rasyid Munthe; Angga Putra Juledi (Politeknik Bisnis Indonesia, 2023)
This research aims to build a Decision Support System (SPK) to choose the best car salon in the Rokan Hilir area. With increasing car ownership, the need for efficient maintenance has become crucial. The Weighted Aggregated Sum Product Assessment (WASPAS) method is used in this SPK. The research stages involve determining criteria, data collection, normalization, determining criteria weights, ranking alternatives, and evaluation. The criteria used in this research consist of price, quality, performance, technology and comfort. Of the nine alternatives, the ranking results show that SM04 is the best salon in the area. The final results of data processing using the WASPAS method in this study obtained 3 alternatives with the largest value, namely rank 1 alternative SM04 with a final result of 0.92715, rank 2 alternative SM02 with a value of 0.92448 and rank 3 alternative SM06 with a value of 0.92101. Through a decision support system for selecting the best car salon using the WASPAS method in the Rokan Hilir area, this design can make a positive contribution in helping vehicle owners make the best decisions, increase decision-making efficiency, and have a positive impact on the car salon industry in the Rokan Hilir area.